[BP.11.05] URIC ACID AND HYPERTENSION. ROLE OF RENIN ANGIOTENSIN AND SYMPATHETIC NERVOUS SYSTEMS ACTIVITY. (September 2017) - Fania, C.; Saladini, F.; Mos, L.; Bortolazzi, A.; Zanata, G.; Garavelli, G.; Casiglia, E.; Palatini, P.
Abstract : Objective: A number of studies have documented an association of serum uric acid (SUA) with risk of hypertension. We did a prospective study to investigate whether SUA was an independent predictor of risk of hypertension in the young and whether plasma renin activity (PRA) and office and ambulatory heart rates differed according to SUA tertile. Design and method: The study was conducted in a cohort of 1156 young-to-middle-age subjects screened for stage 1 hypertension and followed for a median of 11.4 years. Mean age was 33.0 ± 8.6 years and mean office blood pressure at screening was 145.3 ± 10.6/93.4 ± 5.8 mmHg. PRA was measured in 799 participants. In multivariable Cox analyses, data were adjusted for age, gender, body mass index, parental hypertension, 24-hour systolic and diastolic BP, serum creatinine, and lifestyle factors. Results: At follow-up end, 63.3% of study participants developed hypertension needing treatment. SUA was an independent predictor of future hypertension (p = 0.005). Participants with SUA >5.60 mg/dL (top tertile) had a 31% (95%CI, 6%-60%) increase in risk compared to those of the bottom tertile (SUA <4.32 mg/dL). Office heart rate, average 24-hour heart rate, and night-time heart rate significantly increased across SUA tertiles (p = 0.008, p = 0.033, and p = 0.007, respectively, for ANCOVA after adjusting for age, sex, and lifestyle factors). PRA adjusted for age, sex, smoking, coffee and alcohol use increased on going from the first to the third SUA tertile (mean ± SEM, 3.1 ± 0.5, 3.8 ± 0.4, and 4.9 ± 0.5 ng/ml/h, respectively, p = 0.038). Inclusion of physical activity in the model slightly attenuated the relationship (p = 0.044). PRA was lower in active than in sedentary participants (3.2 ± 0.7 versus 4.8 ± 0.4 ng/ml/h, p = 0.050) as were office and ambulatory heart rates (both p < 0.001). No association between SUA and risk of hypertension was found among the active participants (p = 0.71). Conclusions: In keeping with our previous results, these data confirm that SUA is an independent predictor of hypertension in young-to-middle-age subjects. This may be due to the unfavourable effect of SUA on several factors including sympathetic tone and renin-angiotensin-system activity. Regular physical activity can counteract these pathophysiological mechanisms and prevent the development of hypertension in hyperuricemic subjects.